LARVICIDAL EFFECT OF Coffea arabica L., Camellia sinensis (L.) Kuntz, AND Punica granatum L. ON Aedes albopictus (Skuse), THE VECTOR OF DENGUE AND CHIKUNGUNYA - SOM, DIPAK KUMAR; LAHA, PALLABI; MONDAL, SUPRIYA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The purpose of the present study is to envisage the larvicidal activities of three common plant extracts in controlling Aedes albopictus (Skuse), a potential vector of Dengue and Chikungunya. Chloroform extract of green coffee beans, Coffea arabica L.; methanol extract of green tea leaves, Camellia sinensis (L.) Kuntz and chloroform extract of pomegranate fruit peel Punica granatum L. were tested against late 3rd instar/ early 4th instar larvae of Ae. albopictus under laboratory condition following WHO methodology, 2005. LC50 values were determined using the probit analysis with 95% confidence limit. The result indicated that after 24 hours and 48 hours of treatment, LC50 values for green coffee bean extract, green tea leaves extract and pomegranate fruit peel extract against Ae. albopictus larvae were 0.08, and 0.06, 0.13 and 0.06, 0.09 and 0.06 respectively. Our findings revealed that chloroform extract of green coffee beans and methanol extract of green tea leaves are the most effective in controlling Aedes albopictus larvae showing 100% mortality after 48 hours of exposure than chloroform extract of pomegranate fruit peel that shows 66% mortality after 48 hours of treatment. The overall larvicidal trend with reference to LC50 after 24 hours and 48 hours was green coffee > green tea > pomegranate. The larvae exposed to green coffee bean crude extract showed deformities related to moulting behavior and larval morphology. As these plants are widely distributed in India, their formulation might manifest effective eco-friendly alternatives for combating this upcoming potential vector of Dengue and Chikungunya.